Validation of Mental Calculation Strategy Questionsfor Phase A Elementary School Students - Eni Mulyani; Zetra Hainul Putra; Jesi Alexander Alim; Yesi Martha Afrillia (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2026)
Mental calculation strategy is essential for developing young learners’ number sense, flexibility, and efficiency in arithmetic. However, assessment instruments specifically designed to evaluate mental calculation performance in Indonesian primary education remain limited. This study aimed to develop and conduct a preliminary psychometric evaluation of an instrument for assessing second-grade students’ performance on mental calculation tasks in addition and subtraction. Using a quantitative approach with a preliminary instrument development and psychometric testing design, the study involved 34 second-grade students from Witama Nasional Plus Elementary School, Pekanbaru. The instrument consisted of 30 written items, including context-free and context-based tasks. Data were analyzed using item-total correlation, Cronbach’s Alpha, item difficulty, and point-biserial discrimination. The results showed that 20 items were valid and the instrument achieved acceptable internal consistency (Cronbach’s Alpha = 0.747). Most items were of moderate difficulty, while the discriminating power ranged from poor to very good. These findings indicate that the instrument has promising initial psychometric quality, although several items require revision before broader validation and application.